Gambaran Uji Saring HIV Metode Chemiluminescence Immunoassay (ChLIA) pada Darah Pendonor - Tsuraya Nabilah Al Hasna'; Fransica Romana Sri Supadmi (Jaringan Laboratorium Medis, 2021)
Human Immunodeficiency Virus (HIV) is one of the transmitted infection through blood transfusion. Chemiluminescence immunoassay for HIV testing is performed to ensure the safety and quality of blood product that released. Purpose of the study to identify the result of Chemiluminescence Immunoassay methode for HIV testing to blood donor’s characteristic based on gender, age, blood group, HIV titer, and donation location. The design of this research is descriptive retrospective. There is 11 (0,8%) reactive blood bag and 1.289 (99,2%) blood bag non reactive to HIV, reactive blood bag based of gender is 8 (72,7%) blood bag from male donors and 3 (27,3%) blood bag from female donors. Based on donors age, mostly reactive result are from 41-70 years old is 4 (36,4%) donors, and the fewest is from (under) 19 years old is 1 (9,1%) donors. The majority based on blood group is B Rh+ is 4 (36,4%) donors. The majority based on HIV titer is low titer, 1,0-2,0 is 7 (63,6%) donors. Based on donation location, mostly from mobile unit (MU) is 8 (72,7%) donors over 11 donors with HIV reactive. Conclusion of this study is donors gender, donors age, and donation location had a significant influence on reactive result of HIV testing.